1991
DOI: 10.1093/ajcn/53.5.1230
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-linolenic acid is as effective as oleic acid and linoleic acid in lowering blood cholesterol in normolipidemic men

Abstract: The effect of dietary oleic acid (OA), linoleic acid (LA), and linolenic acid (LNA) on plasma lipid metabolism was studied in eight normolipidemic men. A mixed-fat diet composed of conventional foods was fed during 6-d pre- and post-experimental periods. The same basic diet but with 75% of the fat (26% of total energy) provided by sunflower and olive; canola; soybean; and sunflower, olive, and flax oils was fed during four 18-d experimental periods. Mean plasma total cholesterol (-18%), low-density-lipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
55
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(67 citation statements)
references
References 46 publications
8
55
0
4
Order By: Relevance
“…Alternatively, from the analyses of Figure 3, a-linolenic might be involved in preventing the conversion of VLDL to LDL. In any event, these results agree with the previous findings that the consumption of a-linolenic acid has a lowering effect on the serum cholesterol concentration where there are considerable amounts of alinolenic acid available (Chan et al, 1991;Valsta et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, from the analyses of Figure 3, a-linolenic might be involved in preventing the conversion of VLDL to LDL. In any event, these results agree with the previous findings that the consumption of a-linolenic acid has a lowering effect on the serum cholesterol concentration where there are considerable amounts of alinolenic acid available (Chan et al, 1991;Valsta et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…The hypercholesterolemic effect of saturated fatty acids and the hypocholesterolemic effect of some unsaturated fatty acids are well established (Chan et al, 1991). In this study, the total SFA concentration of fatty acids in breast and thigh meat decreased in response to combined treatment of karaya saponin and R. capsulatus in the basal diet.…”
Section: Discussionmentioning
confidence: 58%
“…Feeding studies with fatty acids (Lu et al, 1997;Perez-Jimenez et al, 1995;Abbey et al, 1994;Cobb & Risch, 1993;Chan et al, 1991), fat restriction (Lefevre et al, 1997;Jenkins et al, 1997;Miller et al, 1998;Schaefer et al, 1995), psyllium (Ganji & Kies, 1996), or phytosterols (Pelletier et al, 1995), have shown that serum total cholesterol can be reduced in subjects with comparable or even lower mean serum cholesterol levels. Also, the subgroup with a mean total cholesterol level of 5.7 mmolaL (220 mgadL) did not respond to Lactobacillus acidophilus either.…”
Section: Discussionmentioning
confidence: 99%